Mapping seedling and adult plant leaf rust resistance genes in the durum wheat cultivar Strongfield and other Triticum turgidum lines - Bokore, Firdissa E.; Boyle, Kerry; Ruan, Yuefeng; McCartney, Curt; Hiebert, Colin W.; Knox, Ron; Xiangyu Pei; Reimer, Elsa; Ammar, Karim; Wentao Zhang; Fobert, Pierre; Cuthbert, Richard D.; et al. (American Phytopathological Society, 2024)
Durum wheat (Triticum turgidum) is threatened by the appearance of new virulent races of leaf rust, caused by Puccinia triticina, in recent years. This study was conducted to determine the leaf rust resistance in a modern Canadian durum cultivar, Strongfield. Six populations derived from crosses of Strongfield with six tetraploid wheat lines, respectively, were tested at the seedling plant stage with different P. triticina races. Two of the populations were evaluated for adult plant leaf rust infection in Canada and Mexico. A stepwise regression joint linkage quantitative trait locus (QTL) mapping and analysis by MapQTL were performed. Strongfield contributed the majority of QTLs detected, contributing seven QTLs detected in field tests and eight QTLs conditioning seedling resistance. A 1B QTL, QLr-Spa-1B.1, from Strongfield had a significant effect in both Canadian and Mexican field tests and corresponded with Lr46/Yr29. The remaining field QTLs were found in only the Canadian or the Mexican environment, not both. The QTL from Strongfield on 3A, QLr-Spa-3A, conferred seedling resistance to all races tested and had a significant effect in the field in Canada. This is the first report of QLr-Spa-3A and Lr46/Yr29 as key components of genetic resistance in Canadian durum wheat. KASP markers were developed to detect QLr-Spa-3A for use in marker-assisted leaf rust resistance breeding. The susceptible parental lines contributed QTLs on 1A, 2B, and 5B that were effective in Mexican field tests and may be good targets to integrate into modern durum varieties to improve resistance to new durum virulent races.